The Use of Internal and External Environmental Analysis in Strategic Management at SMPN 1 Laubaleng, North Sumatra Province - Ribka Hernita Sitepu; Hilmi Saputri Nasution; Eka Daryanto; Rosnelli (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the use of internal and external environmental analysis in Strategic Management at SMPN 1 Laubaleng, North Sumatra Province. The external environment and the internal environment have a fairly important role in decision-making efforts to realize the school's vision and mission. This study uses descriptive qualitative research methods by utilizing data in the form of documents, observations and interviews. In addition, literature studies are also used to support existing theories. SMPN 1 Laubaleng has 566 students, consisting of 242 male students and 324 female students, meanwhile, there are 31 teachers, with 18 classrooms. This represents great potential in the region to advance education. There are still many weaknesses in utilizing the results of internal and external environmental analysis, this can be seen in the still not optimal quality of education at SMPN 1 Laubaleng.